Improving electromagnetic properties of FeCoNiSi0.4Al0.4 high entropy alloy powders via their tunable aspect ratio and elemental uniformity. (5th July 2018) - Zhang, Bin; Duan, Yuping; Cui, Yulong; Ma, Guojia; Wang, Tongmin; Dong, Xinglong
Abstract: Mechanical milling and melting-strip casting-milling have been used to prepare FeCoNiSi0.4 Al0.4 high entropy alloy (M-HEA and C-HEA respectively) powders. Both techniques have different solution and phase formation rules. The M-HEA powders have more FCC, and the opposite is true for C-HEA powders. In addition, the C-HEA powders have better elemental uniformity and a larger aspect ratio. Because of this, the C-HEA powders have a smaller M s and a larger H c ; the M s range from 93.6 emu/g to 104.4 emu/g, and the H c vary from 81.5 Oe to 159.6 Oe. As the milling time increases, the variety of aspect ratios and uniformity give rise to the change of electromagnetic (EM) parameters for both HEA powders. Versus the EM parameters of M-HEA powders (ranging from 7.5 to 16 and from 0 to 1.4 for ε' and ε", respectively), these C-HEA powders have larger values (ranging from 11 to 26 and from 0 to 8 for ε' and ε", respectively). At the same time, the μ' (varying from 1.78 to 1.90 at 2 GHz) and the μ″ (up to 0.52) of C-HEA powders are larger than the M-HEA powders. Graphical abstract: Unlabelled Image Highlights: The mechanical milling method and melting-strip casting-milling method have been designed to prepare FeCoNiSi0.4 Al0.4 HEA powders. During this two kinds of technologies, the rules of dissolution and phase formation are different. It has been proven that the C-HEA powders possess better uniformity and larger aspect radio than M-HEA powders. The variety of aspect radio and uniformity lead to the change of electromagnetic parameters for both kinds of HEA powders.